What are the Attitudes of Medical Students at Jazan University Toward Professionalism? - Mustafa M; Terair S; Al Ageeli E; Gohal G; Salih S (Advances in Medical Education and Practice, 2023)
Mai Mustafa,1,2 Salaheldin Terair,2 Essam Al Ageeli,3 Gassem Gohal,1 Sarah Salih4 1Pediatric Department, Faculty of Medicine, Jazan University, Jazan, Jazan, Kingdom of Saudi Arabia; 2Medical Education Department, Faculty of Medicine, Jazan University, Jazan, Jazan, Kingdom of Saudi Arabia; 3Cinical Biochemistry Department, Faculty of Medicine, Jazan University, Jazan, Jazan, Kingdom of Saudi Arabia; 4Family and Community Medicine Department, Faculty of Medicine, Jazan University, Jazan, Jazan, Kingdom of Saudi ArabiaCorrespondence: Mai Mustafa, Pediatric Department, Faculty of Medicine, Jazan University, Jazan, Jazan, Kingdom of Saudi Arabia, Email maiuk96@gmail.comPurpose: We assessed the attitudes of Jazan University medical students toward professionalism and evaluated the associations of those attitudes with demographic factors.Materials and Methods: Seven hundred ninety-seven respondents (88.85% response rate) out of 898 students who were invited to this study (50.7% were men and 49.3% were women) were studied by their response to the Learner’s Attitude of Medical Professionalism Scale (LAMPS) that assess their level of agreement with 28 items, each reflecting a single professionalism competency within the subscales of Altruism, Excellence, Duty/Accountability, Honor/Integrity, and Respect for Others.Results: Of 797 respondents (88.85% response rate), 50.7% were men and 49.3% were women. Subscales with high agreement scores were Excellence (median, 21.0; range, 6– 30) and Duty/Accountability (median, 21.0; range, 7– 35). Subscales with slightly lower agreement scores were Respect for Others (median, 15.0; range, 5– 25), Altruism (median, 15.0; range, 5– 25), and Honor/Integrity (median, 12.0; range, 5– 25). No sex differences were observed for most subscales; however, men gave higher agreement scores on the Excellence subscale, and compared with year 3 respondents (preclinical phase), year 6 respondents (clinical phase) gave higher agreement scores on the Excellence, Altruism, and Respect for Others subscales.Conclusion: Overall, medical students at Jazan University indicated high agreement with all attitudes to professionalism subscales on the LAMPS.Keywords: professionalism, medical students, Jazan University, students’ attitudes, students’ perception